2007
DOI: 10.4103/0973-6247.28065
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet transfusion in the management of dengue patients in a tertiary care hospital

Abstract: Background and Objective:While medical fraternity globally recognizes the role of platelet transfusion in the management of hospitalized dengue patients the exact indications and situations in which these are to be transfused may vary. Since there is inherent risk associated with the transfusion of blood/blood-component, it is imperative for each institution (or country) to lay their own criteria for transfusion of these blood components. The present study was conducted to lay precise criteria and transfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 1 publication
6
77
3
4
Order By: Relevance
“…In this study most of the patients (88.3%) had classical Dengue fever while DHF and DSS were present in 7.5% and 4.3% patients respectively. The results are similar to a study from Delhi where in Dengue fever was seen in majority while DHF and DSS were seen in 9.3% and 2.2% of the total cases respectively [12]. Liver dysfunction in the form of Transaminasemia (SGOT/SGPT>ULN) was found ubiquitously (98.9%) in our study.…”
Section: Discussionsupporting
confidence: 80%
“…In this study most of the patients (88.3%) had classical Dengue fever while DHF and DSS were present in 7.5% and 4.3% patients respectively. The results are similar to a study from Delhi where in Dengue fever was seen in majority while DHF and DSS were seen in 9.3% and 2.2% of the total cases respectively [12]. Liver dysfunction in the form of Transaminasemia (SGOT/SGPT>ULN) was found ubiquitously (98.9%) in our study.…”
Section: Discussionsupporting
confidence: 80%
“…This is as with the results of a recent study from Punjab done by Chhinaet al (DHF and DSS in 13.6% and 5.1% respectively) and from Delhi done by Makroo et al (DHF and DSS in 9.3% and 2.2% respectively). 7,8 However a few other studies had reported a higher percentage of DHF. 9,10 The mean age of patients in our study was 34.63± 13.28 years, with male to female ratio being near equal.…”
Section: Discussionmentioning
confidence: 96%
“…10 Viral fevers especially from dengue have become a quite common indication for platelet transfusion in India. 11 In all the transfusion there will be chances of transfusion transmitted diseases, allergic reaction and other forms of transfusion reactions leading to increased mortality and morbidity in the patients.…”
Section: Introductionmentioning
confidence: 99%